2009
DOI: 10.1186/1471-244x-9-67
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dropout from treatment for eating disorders: a comprehensive literature review

Abstract: Background: Dropout (DO) is common in the treatment of eating disorders (EDs), but the reasons for this phenomenon remain unclear. This study is an extensive review of the literature regarding DO predictors in EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
241
4
17

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(284 citation statements)
references
References 71 publications
(115 reference statements)
14
241
4
17
Order By: Relevance
“…Finally, it has been postulated that persons with an immature defense style will respond less effectively to both pharmacological (49) and psychological (48,51,52) treatment. Lower scores on SD was also previously related with less response to treatment (53,54). Consistent with this, in a previous study SD was found to be lower in short-term abstinence patients who may be perceiving higher levels of stress and use non-adaptive coping strategies than long-term abstinence group (55).…”
Section: Discussionsupporting
confidence: 75%
“…Finally, it has been postulated that persons with an immature defense style will respond less effectively to both pharmacological (49) and psychological (48,51,52) treatment. Lower scores on SD was also previously related with less response to treatment (53,54). Consistent with this, in a previous study SD was found to be lower in short-term abstinence patients who may be perceiving higher levels of stress and use non-adaptive coping strategies than long-term abstinence group (55).…”
Section: Discussionsupporting
confidence: 75%
“…One of the most recent reviews shows that for ED treatments, the dropout rates ranged from 20 to 51 % for inpatient and from 29 to 73 % for outpatient [3]. Our data are right in the middle of the ranges reported in that review.…”
Section: Discussionsupporting
confidence: 58%
“…In the fields of both primary health care and psychiatric care, patients with comorbid PDs experience poorer treatment outcomes (for recent epidemiologic studies, see [6,7]). Several studies have suggested that patients with cormorbid PDs require specific treatment (For depression: [8,9]; For eating disorders: [10]; For substance dependency: [11]). …”
Section: Introductionmentioning
confidence: 99%